2021
DOI: 10.1080/24749508.2021.1923270
|View full text |Cite
|
Sign up to set email alerts
|

Extending the concept of entropy-negentropy for the assessment of ecological dominance and diversity at alpha, beta and gamma levels

Abstract: Several measures of ecological diversity have been defined at alpha, beta, and gamma levels and less attention has been paid to characterise their ecological dominance. In this paper, we extend the concept of negative entropy (negentropy) for the measurement of ecological dominance and diversity at the three hierarchical levels of community characterization. Negentropy is a measure of energy, and gives a convex curve for binary negentropy function, whereas Shannon's entropy gives a typical concave curve. Simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…There are two indexes widely used in analysis: alpha (α) diversity and beta (β) diversity. Alpha (α) diversity presents the mean species diversity in sites or habitats at a local scale [56], and beta (β) diversity indicates the variation in community compositions [56]. By performing 16S rRNA gene sequencing on fecal samples, most of the existing studies have demonstrated that α diversity experiences a dramatical decrease in the SD group compared with the control group, while β diversity displays different outcomes.…”
Section: The Broken Homeostasis Of Gut Microbiota Caused By Sdmentioning
confidence: 99%
“…There are two indexes widely used in analysis: alpha (α) diversity and beta (β) diversity. Alpha (α) diversity presents the mean species diversity in sites or habitats at a local scale [56], and beta (β) diversity indicates the variation in community compositions [56]. By performing 16S rRNA gene sequencing on fecal samples, most of the existing studies have demonstrated that α diversity experiences a dramatical decrease in the SD group compared with the control group, while β diversity displays different outcomes.…”
Section: The Broken Homeostasis Of Gut Microbiota Caused By Sdmentioning
confidence: 99%
“…Among them, the Chao1 index and ACE index can be used to describe the species abundance of bacteria, while the Shannon index and Simpson index were used to measure the diversity of bacterial community ( Xia and Sun, 2023 ). Compared with the Simpson index, the Shannon index comprehensively takes into account the evenness and richness of the community, and the higher the value is, the greater the diversity is ( Kumar et al., 2023 ). Affected by the species abundance and species evenness in the sample community, under the same species abundance condition, if the species in the community are relatively uniform, the diversity of the community is higher ( Kimbro and Grosholz, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…У роботі [18] автори розширюють поняття негативної ентропії (негентропії) для вимірювання екологічного домінування і різноманітності на трьох ієрархічних рівнях характеристики спільноти. Негентропія є мірою енергії і дає опуклу криву для бінарної функції негентропії, тоді як ентропія Шеннона дає типову увігнуту криву.…”
Section: аналіз останніх досліджень і публікаційunclassified